1976
DOI: 10.1177/004051757604600603
|View full text |Cite
|
Sign up to set email alerts
|

Crosslinking of Cotton through Graft Copolymerization

Abstract: Fabric samples were grafted with binary and ternary mixtures of selected vinyl monomers along with acrylamide onto cotton using ceric ammonium nitrate as catalyst from aqueous solution or emulsion, and subsequently polyacrylamide grafts were methylolated in situ and crosslinked. Except in the case of acrylamide-acrylonitrile treatment, finished fabrics show good wrinkle-recovery properties accompanied by satisfactory retention of breaking- and tear-strength and also very much improved resistance to abrasion. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For many years, the method used to graft monomers on the cellulosic fabric was based on the use of catalysts (such as ceric ion) as initiators of the copolymerization between cellulose and the monomer 5–8. The chief drawback of these methods is the generation of highly toxic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…For many years, the method used to graft monomers on the cellulosic fabric was based on the use of catalysts (such as ceric ion) as initiators of the copolymerization between cellulose and the monomer 5–8. The chief drawback of these methods is the generation of highly toxic wastes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is known that the photo-induced graft copolymerization is useful to get a good surface treatment of polymer films. 7) Ogiwara et al reported that hydrogen peroxide8) and a mixture of methanol and water9) are considerably effective as photosensitizer and solvent, respectively to obtain high grafting in the photoinduced graft copolymerization of methyl methacrylate (MMA) on cellulose.…”
Section: Introductionmentioning
confidence: 99%